Effect of sleep on overnight CSF amyloid-β kinetics - Lucey, Brendan P. (Ann Neurol, 2018)
Sleep disturbances are associated with future risk of Alzheimer’s disease. Disrupted sleep increases soluble amyloid-β, suggesting a mechanism for sleep disturbances to increase Alzheimer’s disease risk. We tested this response in humans using indwelling lumbar catheters to serially sample cerebrospinal fluid while participants were sleep-deprived, treated with sodium oxybate, or allowed to sleep normally. All participants were infused with (13)C(6)-leucine to measure amyloid-β kinetics. We found that sleep deprivation increased overnight amyloid-β-38, amyloid-β-40, and amyloid-β-42 levels by 25–30% via increased overnight amyloid-β production relative to sleeping controls. These findings suggest that disrupted sleep increases Alzheimer’s disease risk via increased amyloid-β production.